PERMINTAAN BERAS KEPALA DI KOTA KENDARI, SULAWESI TENGGARA - SUHARNO - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
Since 2000, the agribusiness of super rice in Kendari city has progress. Severalstore and supermarket sell the super rice. There are many kind of super rice suppliedfrom rice milling firm of near Kendari city especially from Konawe district, thearomatic super rice and non aromatic super rice. Related the condition, implemented theresearch, objectives is to know the factors which influences to super rice demand inKendari city. The research implemented on several store which sell the super rice inKendari city on December 2003. Researh method on the reasearh is survey to gatherprimary data on super rice marketing and collecting relevance data on governmentinstitutions. The research result indicated that the demand of aromatic super riceinfluenced by variabel : population income, and other rice price. Population incomesignificantly influence of demand, it is showed 3,57. The other rice price significantlyinfluenced to aromatic super rice rice demand it is showed 9,23. The total populationsignificantly influenced to non aromatic super rice demand it is showed 2,14. The otherrice influenced to non aromatic super rice demand it is showed 3,61. The result ofresearch suggested to super rice producent that consument more like to choose thepackage with volume 5 kg than bigger package.